The King & Matt O'Mulshon - Scott, Hugh (Hambleside Publishers Limited, 1983)
A Loaf flew over the battlements and hit the King on the Ear.The thinks somebody does not like him and finds out who it was.
Keywords: Juvenile literature-Fiction